Zakah Rate In Islamic Stock Performance Models: Evidence From Indonesia - Qudratullah, Mohammad Farhan (Ekonomi Syariah IAIN Kudus, 2020)
There are three models commonly used to measure the performance of Islamicstocks, named Treynor Ratio, Sharpe Ratio, and Jansen Index. One component of the three models is risk-free returns which are usually approached with interest rates, whereas interest rates are prohibited in the concept of Islamic finance. This paper will approach a risk-free return with zakat-rate on the Islamic capital market in Indonesia from January 2011 - July 2018, then compare it with a model that uses interest rates. The results obtained by the model with interest rates and zakah-rate in this third model have very high suitability values, so that zakah-rate can be used as an alternative substitute for interest rates in measuring the Islamic stock performance. Beside not contradicting the concept of Islamic economics, calculation of models with zakah-rate is simpler than models with interest rates.